Convergent validity, reliability, and sensitivity of a running test to monitor neuromuscular fatigue - Leduc, C.; Tee, J.; Lacome, M.; Weakley, J.; Cheradame, J.; Ramirez, C.; Jones, B. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the convergent validity, reliability, and sensitivity over a week of training of a standardized running test to measure neuromuscular fatigue. Methods: Twenty male rugby union players were recruited for the study, which took place during preseason. The standardized running test consisted of four 60-m runs paced at ~5 m·s-1 with 33 seconds of recovery between trials. Data from micromechanical electrical systems were used to calculate a running-load index (RLI), which was a ratio between the mechanical load and the speed performed during runs. RLI was calculated by using either the entire duration of the run or a constant-velocity period. For each type of calculation, either an individual directional or the sum of the 3 components of the accelerometer was used. A measure of leg stiffness was used to assess the convergent validity of the RLI. Results: Unclear to large relationships between leg stiffness and RLI were found (r ranged from -.20 to .62). Regarding reliability, small to moderate (.47-.86) standardized typical errors were found. The sensitivity analysis showed that the leg stiffness presented a very likely trivial change over the course of 1 week of training, whereas RLI showed very likely small to a most likely large change. Conclusions: This study showed that RLI is a practical method to measure neuromuscular fatigue. In addition, such a methodology aligns with the constraint of elite team-sport setup due to its ease of implementation in practice.